Resiliencia y reconstrucción: lecturas sobre vulnerabilidad y el impacto de violencia de género (2019-2021) - Perusset, Macarena (2023)
This paper determines the path followed by Flavia, a woman victim of gender-based violence, who left her home in the province of La Rioja and moved to a small community in the northwest of the province of Córdoba, Argentina, with her two daughters. Based on the ethnographic work carried out, we analyze the search for and construction of a home from the vulnerability approach. The fieldwork allows us to explore how women and their families which have experienced situations of gender-based violence live in «vulnerable homes» and were able to rebuild themselves by relying on family ties and social support networks in order to rebuild a home. This work also allows us to observe how the notion of vulnerability was used in different situations or scenarios as a moral and bureaucratic resource both, by public authorities to select those to protect, and by vulnerable people, to claim their rights. Vulnerability emerges as a space of experience in which people learn to navigate and in which distress, creativity and social support networks overlap.